Sangguniang Kabataan (SK) Programs at Esperanza, Agusan Del Sur: Influence on Youth Development - Perez, John Carlo L.; Clamo, Leonila (RIRAI Publisher, 2025)
This study examined the effectiveness of the Sangguniang Kabataan (SK) programs implemented in schools across Esperanza, Agusan del Sur, emphasizing their impact on youth development. The research aims to evaluate how well these programs are meeting their objectives, particularly in the areas of health, education, social inclusion, peacebuilding, active citizenship, and economic empowerment. A quantitative research design was employed using a structured survey questionnaire distributed to youth participants engaged in SK programs. Data collection focused on assessing perceived program effectiveness and its correlation with key youth development indicators. Descriptive statistics, mean analysis, and regression analysis were utilized to analyze the data. Results show that SK programs were highly effective, consistently earning high implementation ratings. Notably, leadership (mean = 3.63) and problem-solving (mean = 3.65) were the most strongly developed competencies among participants. The study found that the programs significantly fostered confidence, enabling youth to plan, take initiative, and manage responsibilities. The study concludes that regular program evaluation, capacity-building for SK leaders, and policy refinement are essential steps to sustain and further improve the impact of these youth-centered initiatives. Strengthening these aspects will not only maximize the programs' potential but also ensure that the youth are effectively empowered to contribute meaningfully to their communities and society at large.